Bioarchaeology of care through population-level analyses - Schrenk, Alecia A.; Tremblay, Lori A. (University of Florida Press, 2022)
"Representing current and emerging methods and theory, this volume introduces new avenues for exploring how prehistoric and historic communities provided healthcare for their sick, injured, and disabled members."--